Principles of Maritime Power - Elleman, Bruce A., 1959- (Rowman & Littlefield Publishers, 2022)
"This concise but exhaustive treatment of sea powers examines the strengths and weaknesses of maritime power, including chapters on mutiny, blockades, coalitions, expeditionary warfare, piracy, commerce raiding, and soft power operations. Throughout, Elleman analyzes the competition between land power and sea power strategies"--